Effects of Methanol on the Treatability of Black Liquor using UASB Reactor (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
This study was conducted on a laboratory scale UASB (upfow anaerobic sludge blanket) reactor, treating an actual pulping effluent at an organic loading rate and hydraulic retention time of 2.1 kg-COD/m3d and 44 hours, respectively. To investigate the impacts of methanol, it was subjected to the reactor with the feeding solution (substrate) in concentration ranging from 100 mgTOC/l to 700mgTOC/l. It was observed that the overall TOC and COD removal efficiency of the reactor was improved gradually from 36% and 34% to 57% and 55%, respectively, by increasing the concentration of methanol up to 600 mgTOC/l, but very little effects of methanol on the removal efficiency of lignin were observed. The lignin removal efficiency of the reactor slightly changed from 25% to 31%. The gas conversion rate was found to be improved slightly from 0.31[L-CH4/g-CODrem.day] to 0.34 [L-CH4/g-CODrem.day], with an average methane composition of 61%. Hence, addition of methanol to the reactor can improve the black liquor degradation up to certain extent.Key words: Black liquor; Methanol; UASB; Lignin; TOCDOI: 10.3126/hn.v6i0.4193Hydro Nepal Vol. 6, January 2010Page: 42-46Uploaded Date: 24 January, 2011